Respon Pertumbuhan Bibit Single Bud Tanaman Aglaonema Varietas Donna Carmen Terhadap Aplikasi Zat Pengatur Tumbuh dan Pupuk Daun - Munandar, Denna Eriani; Rifeni, Meyga Ridi (Jember University Press, 2024)
Ornamental plants now become a trend among the public. The hobby of growing ornamental plants causes the demand for ornamental plant is increased day by day, especially the Aglaonema ornamental plant. In general, the propagation of Aglaonema plants is carried out by using separation of tillers and stem cuttings of 4-7 segments. Due to the high demand for Aglaonema plants, a new method of plant propagation is needed, in order to produce more plants in a short time, by using the single bud nursery method. Aglaonema stem cuttings are difficult to do because Aglaonema plants has bud's dormancy period. Dormancy of Aglaonema plant buds is triggered by apical dominance. The way to break bud dormancy on Aglaonema cuttings is using zpt auxin (Rootone-f). In addition, plants also need nutrients to grow, by providing fertilizer. Fertilization for ornamental plants generally uses foliar fertilizer (Gandasil D). This research was conducted using a Randomized Block Design (RBD) which consisted of 2 factors, the first factor zpt auxin (Rootone-f) which consisted of 4 levels (0 ppm, 100 ppm, 200 ppm, 300 ppm), and the second factor was Gandasil D foliar fertilizer which consisted of 3 treatment levels (0 g/l, 1 g/l, 2 g/l) so there are 12 treatment combinations. Each combination was repeated 3 times, thus forming 36 experimental units. The data were analyzed by analysis of variance (ANOVA) to determine the effect of the treatment and those whose effects were significantly different were further tested using the Ducan Multiple Range (DMRT) with a 95% confidence level. The combination of auxin zpt treatment (Rootone-f) with a concentration of 200 ppm and Gandasil D foliar fertilizer with a concentration of 2 g/l showed the best treatment combination on the parameters of observing fresh weight of Aglaonema plants. The concentration of zpt auxin (Rootone-f) 200 ppm gave the highest average value of shoot length, number of leaves, root length, and number of roots of Aglaonema plants. The concentration of Gandasil D 2 g/l foliar fertilizer gave the highest average leaf length and leaf width of Aglaonema plants.